José de Alencar, um escritor-crítico no limiar da modernidade - Kiefer, Charles (Navegações, 2013)
Este estudo trata de duas polêmicas: uma, do passado; outra, do presente. A do presente polemiza a questão da metrificação das produções acadêmicas na atualidade; a do passado relembra a diatribe de José de Alencar contra Gonçalves de Magalhães. O autor deste ensaio demonstra a “cientificidade” da análise de José de Alencar quanto ao poema épico “A confederação dos Tamoios”. ..................................................................... Abstract: Keywords: This essay addresses two controversies: one from the past, another hta belongs to the present. The first one deals with the criticism of José de Alencar against Gonçalves de Magalhães, the second one is about the versification of academic productions today, the second one reminds text by José de Alencar against Gonçalves de Magalhães. The author of this essay demonstrates the “scientific” analysis of José de Alencar on the epic poem “The confederation Tamoios”.Controversy; Epistolography; History of literature; Classical literature; Romantic Literature; Nationality